The Finnish EMU buffers and the labour market under asymmetric shocks - Kari E. O. Alho (The Research Institute of the Finnish Economy (ETLA), 2004)
The Finnish EMU buffers consist of elements built into the unemployment insurance and employment pension systems, which aim to stabilise employer contributions and employment during economic fluctuations in the EMU age. The paper simulates the role of these buffers in a hypothetical recession caused by an adverse asymmetric shock. The results show that the buffers play only a modest role in stabilising employment, although their importance increases as the shocks to the economy become greater. On the other hand, the buffers are likely to entail behaviour of the moral hazard kind, as they reduce the need for real wage adjustment in the economy. The paper also addresses the policy problem of whether to manage a recession by cutting employers' indirect labour costs or by raising effective demand through increased social security benefits. A criterion for this policy choice is derived and tested using Finnish data. – – Suomen EMU-puskurit koostuvat työeläkejärjestelmään ja työttömyysvakuutusjärjestelmään kootuista puskureista. Niiden tavoite on pitää yritysten sosiaalivakuutusmaksut vakaina mahdollisissa taantumissa EMU-oloissa ja siten vakauttaa työllisyyskehitystä verrattuna jakojärjestelmään. Tämä paperi analysoi ensin puskureiden merkitystä työllisyyden vakauttajana kuvitelluissa taantumissa. Tulos on se, että puskureiden merkitys on suhteellisen vähäinen tässä suhteessa, mutta kuitenkin sitä merkittävämpi, mitä pahempi taantuma on. Toiseksi arvioidaan sitä, onko puskureilla ns. moraalikadon ominaisuus, koska ne voivat vähentää muuten toteutuvaa reaalipalkkasopeutumista työmarkkinoilla. Kolmanneksi tutkitaan sitä, minkälaista talouspolitiikkaa pitäisi noudattaa taantumassa, so. pitääkö karsia yritysten välillisiä työvoimakustannuksia vähentämällä työttömyysetuuksia vai ylläpitää kysyntää lisäämällä sosiaalietuuksia ja rahoittaa ne yritysten työttömyysvakuutusmaksuilla. Tämän politiikkavalinnan suhteen johdetaan kriteeri ja sen paikkansapitävyyttä analysoidaan empiirisesti Suomen aineistolla.
Keywords: 330; EMU buffers; asymmetric shock; wage formation; EMU-puskurit; epäsymmetriset shokit; palkanmuodostus; Arbeitsmarkt; Europäische Wirtschafts- und Währungsunion; Finnland